Linear codes and cyclic codes over finite rings and their generalizations: a survey - Djoko Suprijanto (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2023)
We survey a recent progress of cyclic codes over finite rings and their generalization to skew cyclic as well as skew cyclic codes with derivation over finite rings, focusing on structural properties of the codes. We also report recent developments on the construction methods of linear codes from graphs, in particular strongly regular as well as distance regular graphs.